Genetic Mapping of a Major Resistance Gene to Pea Aphid (Acyrthosipon pisum) in the Model Legume Medicago truncatula - Kamphuis, Lars G. (Int J Mol Sci, 2016)
Resistance to the Australian pea aphid (PA; Acyrthosiphon pisum) biotype in cultivar Jester of the model legume Medicago truncatula is mediated by a single dominant gene and is phloem-mediated. The genetic map position for this resistance gene, APR (Acyrthosiphon pisum resistance), is provided and shows that APR maps 39 centiMorgans (cM) distal of the A. kondoi resistance (AKR) locus, which mediates resistance to a closely related species of the same genus bluegreen aphid (A. kondoi). The APR region on chromosome 3 is dense in classical nucleotide binding site leucine-rich repeats (NLRs) and overlaps with the region harbouring the RAP1 gene which confers resistance to a European PA biotype in the accession Jemalong A17. Further screening of a core collection of M. truncatula accessions identified seven lines with strong resistance to PA. Allelism experiments showed that the single dominant resistance to PA in M. truncatula accessions SA10481 and SA1516 are allelic to SA10733, the donor of the APR locus in cultivar Jester. While it remains unclear whether there are multiple PA resistance genes in an R-gene cluster or the resistance loci identified in the other M. truncatula accessions are allelic to APR, the introgression of APR into current M. truncatula cultivars will provide more durable resistance to PA.